PDF PENGARUH PAKAN TERHADAP KANDUNGAN LEMAK TIDAK JENUH, STABILITAS LEMAK, DAN WARNA DAGING SELAMA PEMAJANGAN : REVIEW Feed Effect on Unsaturated Fat Content, Fat Stability, and Meat Color During Display : Review: RIA ANJALANI - journal journal (Agrienvi: Jurnal Ilmu Pertanian, 2019)
ABSTRACTMeat is an animal product that contains fat, especially saturated fat. The saturated fat contentof the meat affects the shelf life and freshness of the meat during storage. This paper discusses waysto increase the content of unsaturated fats in meat, as well as improving the stability of fat and meatcolors during storage through feeding during on farm management, so that the meat sold meets thetastes of consumers.Keywords : Feed, Meat, Unsaturated Fat, Fat Stability, Meat Color, Display